Procedimentos do ensino da leitura no primeiro ano do ensino fundamental: concepções, estratégias e resultados - Lopes, Janaina de Almeida [UNESP] (2016)
The theme of the reading in the first year of the literacy cycle has become recurrent in academic papers, research groups, discussion forums, conferences etc. and raised different positions depending on the theoretical framework with which it is studied. While it is granted that reading instruction this school year is to ensure the ability to encode and decode and learn and understand the meanings and the meanings of what we read. In this work, it formed a general objective to investigate how reading skills are being developed in the classroom and the strategies used to develop decoding and understanding of meanings. The question that formed the north to the survey was as follows: The strategies and procedures being used in the teaching of reading in the early literacy process develop the coding and decoding skills beyond the grasp and understanding of the meanings of ideas? The specific objectives were established: a) investigate how is the teaching of reading in the first grade of elementary school; b) identify the teaching strategies and the design of reading and reader that the teacher of the class has observed and relate it to the way he teaches; c) verify that the teaching of reading in the first year of the literacy process, develop the early reading skills, decoding, and favors the development of the apprehension and understanding of the meanings of what we read. The methodology included field research, from a qualitative interpretation approach and had as direct data source the natural environment in which the teaching of reading has been developed. The work then displays data results analyzed in the light of literacy concepts distinguished by Soares (2011), and reading by Silva (1983), Foucambert (1994), Solé (1998), among others. The results were extracted inferences and interpretations. It is hoped that this work raises in literacy teachers, reflections on the teaching of reading in the literacy cicle, in order to establish the...